Font of pardon and new life: John Calvin and the efficacy of baptism - Bierma, Lyle D. (Oxford studies in historical theology, 2021)
'Font of Pardon and New Life' is a study of the historical development of John Calvin's doctrine of baptism, both adult (or believer) baptism and infant baptism. In a chronological examination of Calvin's writings - his Institutes, commentaries on the Bible, catechisms, polemical treatises, and consensus documents - the book addresses the question of what, in Calvin's view, spiritually takes place in an individual when he or she is baptized, and it analyzes the impact of Calvin's baptismal doctrine on the major Reformed confessions and catechisms of the sixteenth and seventeenth centuries.